Spatial Inequality and Accessibility of Senior High School Education in Bonebolango Regency - Bakari, Aljunaid; Sidik, Firman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze the spatial dynamics of upper secondary education services, distribution patterns, and the reach of high school services in Bonebolango Regency. The research method used in the study was spatial descriptive, with data sources from schools and the Central Statistics Agency. The data analysis techniques used are meeting needs, school occupancy levels, and utilizing the Geographic Information System (GIS) through the analysis of the nearest neighbors, buffers, and overlays. The results of this study show that the availability of high school facilities in Bonebolango Regency has not met the needs of the upper school-age community, because it has not been able to accommodate 80% of the high school age population in each sub-district. The occupancy rate is also uneven, with four high schools having an occupancy rate above 80% of the temporary capacity and 11 high schools having an occupancy rate of less than 50% of their capacity Based on the analysis of the nearest neighbors, the distribution pattern of high schools in Bonebolango Regency is relatively random, with a value of 0.975337 and a z-score of -0.030915. Based on the analysis of the service coverage of high school facilities using the buffer method according to SNI 03-1733-2004, it is known that high school facilities in Bonebolango Regency are very uneven and tend to overlap in several sub-districts and do not cover all settlements.